دور المحتســب في حمــــــــايــــــــة البيئــــــــــــة (El-Wahat Journal for Research and Studies, 2021)
The Islamic law (Sharia) contains many provisions that demonstrate the extent to which the environmental dimension is taken into account in its provisions, which had led to the emergence of some Islamic systems contributing to the preservation of the environment, one of the most important is the Hisbah system, where in the books of al-Hesba many texts, stating  to confront the Muhtasib with any behavior likely to harm the environment, whether it's about executing oversight on the market or different roads and public places, therefore, this study sheds light on the measures that the Muhtasib takes in his work to preserve the environment, where the study dealt with the definition of the basic concepts of  the research, as it touched identifying the aspect in which the environmental dimension is reflected in muhtasib specialties. Key words- Hisbah system, Muhtasib, Environmental protection, Prohibition of vice, Health preservation, improve environmental health, The beauty of the city.